2018
DOI: 10.1680/jgere.17.00017
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional compression and swelling of compacted fly ash

Abstract: The aim of the paper is to prove that the compressibility and swelling of compacted fly ash in both unsaturated and fully saturated conditions are dependent on the moisture content at the compaction and on the compaction energy, as in the case of cohesive soils. The studies have been conducted on samples compacted at various water contents in conventional oedometers and the Rowe hydraulic consolidation cell and in California bearing ratio moulds (swelling tests). The one-dimensional compressibility of saturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…As the water flows, the sample degree of saturation increases, but it is not certain that the back pressure value used to test partially saturated sample is sufficient to fully saturate the sample. It is shown that the condition of full and partial saturation is also important in determining compression and settlement characteristics of the compacted fly ash [50]. Figure 10 shows the dependency of hydraulic conductivity on effective stress at hydraulic gradient i = 32 of fly ash, fly ash-bentonite mixes and cohesive soil.…”
Section: Hydraulic Conductivitymentioning
confidence: 99%
“…As the water flows, the sample degree of saturation increases, but it is not certain that the back pressure value used to test partially saturated sample is sufficient to fully saturate the sample. It is shown that the condition of full and partial saturation is also important in determining compression and settlement characteristics of the compacted fly ash [50]. Figure 10 shows the dependency of hydraulic conductivity on effective stress at hydraulic gradient i = 32 of fly ash, fly ash-bentonite mixes and cohesive soil.…”
Section: Hydraulic Conductivitymentioning
confidence: 99%
“…Non-plastic silty soils behave like pure sands. Soils macroscopically evaluated as non-cohesive and not demonstrating plasticity may however exhibit properties of cohesive soils, with changes occurring not only in strength characteristics but also in deformation and filtration, which was found in the example of fly ash [6][7][8]. The phenomenon of cohesion resistance in non-cohesive soils is the result of suction in the soil, which is often associated with capillary suction.…”
Section: Introductionmentioning
confidence: 99%
“…The authors' earlier work [6][7][8] has shown that compacted non-plastic fly ash should always be evaluated considering the moisture content at compaction, as in the case of cohesive soils. The aim of the work is to show how the variable content of fine particles in fly ash influences the diversification of its mechanical parameters, which will be shown in the example of the California Bearing Ratio (CBR) of ash as a parameter that is strictly dependent on the initial compaction [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research it has been frequent practice to present the shear strength values of interface contact only for mineral soil compacted at water content closed to optimum. The permeability and mechanical properties of compacted non-cohesive fly ash and fly ash/bottom ash mixture are dependent on moisture content during compaction, w, as are properties of cohesive mineral soils [14]. Consequently, different values are obtained for w on either side of the wopt on a compaction curve, for the same dry densities, ρd.…”
Section: Introductionmentioning
confidence: 99%